(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Spread average degrees of systolic and diastolic arterial pressure (the SAP and DAP) was studied among unorganized population (1574 men and 2395 women) on new epydemiological of the arterial hypertension. The Average degree among of SAP men is 144,8 mm.Hg., among women - 141 mm.Hg., but average degree of DAP among men - 92,3 mm.Hg., among women - 90,2 mm.Hg With increase the age average degree and DAP increase criterions, particularly after 50 years the increase becomes more important